Chalcone isomerase gene from avicennia marina under Salt stress (Bangladesh Journal of Botany, 2026)
Flavonoid accumulation in Avicennia marina under salt stress and the structural and transcriptional characteristics of its chalcone isomerase gene (AmCHI) were investigated. Seedlings were exposed to 0, 200, and 400 mmol/l NaCl. Leaf flavonoid content increased significantly with salinity, concomitant with a concentration-dependent upregulation of AmCHI expression, as confirmed by qRT-PCR. The full-length AmCHI cDNA was cloned and bioinformatically analyzed, revealing a conserved chalcone_3 domain, cytoplasmic localization, and absence of signal peptides. Protein-protein interaction network analysis indicated that AmCHI interacts with core flavonoid biosynthetic enzymes (F3H, F3’H, DFR, ANS, FLS), modification/transport proteins (GSTF12, UGT78D2), and the transcription factor MYB75. These findings suggest that AmCHI enhances flavonoid production under salt stress to alleviate oxidative damage and may coordinate with the MYB regulatory network via protein interactions to bolster salt tolerance in A. marina.Bangladesh J. Bot. 55(1): 53-59, 2026 (March)